Pengembangan Media Kuartet Suku Dan Agama “Sukma” Di Indonesia Muatan Ips Kelas IV SD Negeri 13 Gelumbang - Tarisa Yulianti; Aryaningrum, M.Pd; Hetilaniar, M.Pd (CV. ITTC INDONESIA, 2024)
This development research aims to produce a valid, practical and effective media quartet of tribes and religions